Sustainable food production practices in the Caribbean - 2 - Ganpat, Wayne G.; Isaac, Wendy-Ann P. (CTA / Ian Randle, 2015)
Alternative, sustainable farming and food systems must be encouraged in the Caribbean region if producers are to maintain a supply of healthy food at reasonable prices. This second volume of food production practices and innovative technologies provides a valuable, blended collection of topics not previously covered. Featuring numerous colour images, figures, tables and information boxes throughout, chapters range from a focus on small producers, family farms and women farmers to the role of youth in agriculture and diversification and non-traditional systems. Topics also cover natural and indigenous crop protection methods, small animal systems and sustainable water management systems, among others.